Synthesis and Antibacterial Activity of New Spiro[thiadiazoline-(pyrazolo[3, 4-d]pyrimidine)] Derivatives. (13th May 2015) - El Fal, Mohammed; Ramli, Youssef; Zerzouf, Abdelfettah; Talbaoui, Ahmed; Bakri, Youssef; Essassi, El Mokhtar
Abstract : New heterocyclic compounds spiroderivatives of allopurinol of biological interest were prepared from allopurinol via thionation and 1, 3-dipolar cycloaddition and were produced in high to excellent yields. These compounds were characterized on the basis of spectral and spectroscopic data ( 1 H NMR, 13 C, IR, and MS). The antibacterial activity of the synthesized products was studied using bacterial strains: Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa . Compounds having an ethyl group showed the best activity with MIC value of 31.25  µ g/mL against Staphylococcus aureus and Streptococcus fasciens .